Learning Task Models in the Context of Education for Sustainable Development - Grytsenko, V.I.; Kudriavtseva, S.P.; Synytsya, K.M. (Control systems & computers, 2020)
Purpose. To study how the ideas of sustainable development can be incorporated into the learning content and the instructional process by integrating digital didactics methods, knowledge structuring, and digital technologies. To show by applying a task-based approach, that support for performing the tasks of learning, instruction (teaching) and dialogue in an open learning environment is crucial for achieving the SDGs. Methods: Systems approach, problem theory, problem approach, generalizations. Results: It is demonstrated how lifelong learning, as a basis for the implementation of ESD, and access to knowledge in the digital age can contribute to the achievement of the SDGs. The features of the tasks of teaching, learning and interaction for achieving the SDGs in education have been investigated, the corresponding task models have been formulated. The requirements for the functionality and technologies of an open learning environment which allows learners to achieve the set of goals when solving learning problems in the framework of ESD are described.